2019
DOI: 10.1210/js.2019-sat-lb005
|View full text |Cite
|
Sign up to set email alerts
|

SAT-LB005 Association of Serum Estrogens and Estrogen Metabolites with Use of Non-Steroidal Anti-Inflammatory Drugs in Postmenopausal Women

Abstract: Background: In several recent studies of postmenopausal women, the use of non-steroidal anti-inflammatory drugs (NSAIDs) has been associated with lower circulating estrogens. These analgesics have also been studied in association with breast cancer risks with inconsistent findings. Cross-talk between immune and endocrine factors may play important roles in the development of breast cancer. Methods: We conducted a study of postmenopausal women drawn from the Prostate, Lung, Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study could not assess the duration of NSAID use or dosage information. Furthermore, summarized results of a recent study revealed that more frequent consumption of NSAIDs (aspirin, nonaspirin NSAIDs, or both aspirin and nonaspirin NSAIDs) in postmenopausal women (with or without BC) decreased circulating estrogens and estrogen metabolites [ 34 ]. When the association between aspirin use and estrogen levels was stratified by BMI, the results were sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study could not assess the duration of NSAID use or dosage information. Furthermore, summarized results of a recent study revealed that more frequent consumption of NSAIDs (aspirin, nonaspirin NSAIDs, or both aspirin and nonaspirin NSAIDs) in postmenopausal women (with or without BC) decreased circulating estrogens and estrogen metabolites [ 34 ]. When the association between aspirin use and estrogen levels was stratified by BMI, the results were sparse.…”
Section: Discussionmentioning
confidence: 99%
“…When the association between aspirin use and estrogen levels was stratified by BMI, the results were sparse. A study found that BMI had no effects on the results [ 11 ], whereas some studies did not assess [ 22 , 23 ] or had no clear pattern of interaction with BMI [ 17 ], or data were not available [ 34 ]. Major limitations encountered in these studies contain unavailability of information on the exact frequency of use or dose of aspirin or each NSAID, differences in the definitions of aspirin exposure, measurement of estrogen levels in only one time-point, lack of tissue-specific outcomes, and lack of certainty on the role of confounding factors in lowering estrogen levels.…”
Section: Discussionmentioning
confidence: 99%